Synthesis of Bandpass Filter as a Four-Pole Based on a Non-Homogeneous Line - Kozlovskiy, Valeriy; Kozlovskiy, Valerii; Boiko, Juliy; Balanyuk, Yuriy; Yakymchuk, Natalia (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2024)
The article deals with the synthesis of band-pass filters (BPF) for the design of microwave filtering devices, by using non-homogeneous lines (NL) with the selection of the appropriate wave impedance W. For this purpose, equivalent NL substitution circuits were created in the region of resonant and antiresonant frequencies, and four-pole matrices of the transmission line were determined, whose matrix of impedances and admittances does not have partial poles, and the transmission admittance and transmission impedance do not have zeros. BPF prototypes were synthesized with two parallel plumes based on a closed homogeneous line and one plume based on three NLs. A band-pass filter with an extended blocking band was implemented, and its amplitude-frequency characteristics were obtained. The use of NLs as resonators allows the choice of wave impedance to increase the blocking band of the BPF compared to the BPF on resonators based on homogeneous lines.